Review of bolted inter-module connections in modular steel buildings - Lacey, A.; Chen, Wensu; Hao, H.; Bi, Kaiming (2019)
In current practice, the force-displacement and moment-rotation behaviours of inter-module connections for modular steel buildings are established by a combination of theoretical, experimental, and numerical analyses. The simplified connection behaviour is then incorporated into a numerical model of the overall structure for analysis and design. For engineering design analysis, it is desirable to estimate the inter-module connection stiffness by means of simplified calculations. Methods for estimation of the stiffness of traditional steel connections are available in the literature, however, their application to inter-module connections (also known as inter-connections) remains to be investigated. This paper summarises existing inter-connection details, including their purpose and associated design methods and models. The inter-connections selected from the literature provide details of the typical force-displacement and moment-rotation behaviours. For the selected inter-connections, the numerical and experimental results are compared with the calculated theoretical results predicted by existing theoretical models. The existing theoretical models are compared, and their limitations are outlined.